Urgensi Transformative Justice dalam Penanganan Perkara Anak Sebagai Upaya Pembaharuan Hukum Indonesia - Hakim, Lukman; Endro Purwoleksono, Didik (Jurnal Supremasi, 2024)
This study examines the urgency of transformative justice in handling juvenile cases as part of legal reform in Indonesia. The research employs normative legal methods with statutory, conceptual, and case approaches. The importance of this research lies in identifying the need to expand the concept of restorative justice, which focuses solely on the offender and victim, towards transformative justice that also considers social, political, economic, and cultural aspects. The findings reveal that transformative justice offers a new alternative in the juvenile criminal justice system by not only focusing on the severity of the offense but also considering the personal circumstances of the child, including social status and family conditions. The implications of this concept show that transformative justice supports the more comprehensive development of children and serves as a more holistic approach to recovery in handling juvenile cases.